The early complex correction of thrombophilia in patients with intrauterine growth restriction - L A Ozolinya; I A Lapina (IP Berlin A.V., 2014)
The actual direction of modern public health service is the reduction of the level of diseases in pregnancy. Hypercoagulable state is one of the major causes of complications and often associated with intrauterine growth restriction. The purpose of this study was to determine whether early complex correction of thrombophilia, including vitamins (folic acid, Vitrum Prenatal Forte) and anticoagulation therapy reduce risk of intrauterine growth restriction and pregnancy loss. Materials and methods: 30 pregnant patients with intrauterine growth restriction of different severity level and 30 healthy pregnant women. Thrombophilia of different causes was detected in 60% intrauterine growth restriction. We conclude that the methods of early diagnostics and complex correction of hypercoagulable state in patients with intrauterine growth restriction significantly decrease perinatal morbidity rates.